The perception of banking managers from a municipality in the State of Pará on the internal control in the management of socio-environmental risk (Revista Brasileira de Contabilidade e Gestão, 2022)
Objective(s): This study aims to analyze the perception of managers from financial institutions in the municipality of Tomé-Açu, in the State of Pará, regarding the interaction between internal control and social and environmental risk as a variable in the credit grant analysis process via descriptive research, with qualitative and quantitative approach. Method: Semi-structured questionnaires were applied to bank branch managers located in the municipality of Tomé-Açu, with close- and open-ended questions to collect data that were then tabulated and analyzed using the software SPSS, Excel, and IRAMUTEQ. Results: We concluded that internal control acts as a tool to help the managers of the institutions with risk analysis process, evidencing the social and environmental risk, influencing cultural changes in the organization and evaluation of the social and environmental responsibility policies. The positive perception of managers on the benefits of adopting good internal control in the management of social and environmental risks, acting as an institutional filter, stands out, so that existing risks can be minimized and controlled with the consistent use of internal control procedures. Contributions: We suggest for future surveys to be conducted with a larger number of respondents, with the possibility of extending to borrowers and all internal employees of the financial institution.
Keywords: banking managers; social and environmental risk management; internal control; social and environmental risk; financial institution